A comparative study of selective dry and wet etching of germanium–tin (Ge1−xSnx) on germanium. (12th July 2018) - Han, Yi; Li, Yaoyao; Song, Yuxin; Chi, Chaodan; Zhang, Zhenpu; Liu, Juanjuan; Zhu, Zhongyunsheng; Wang, Shumin
Abstract: A comparative study of selective dry and wet etching methods for germanium–tin (Ge1−x Snx ) alloys (3.5% < x < 7.7%) and germanium (Ge) is carried out. Both etching methods are optimized from the perspectives of selectivity and morphology, and then compared. A special behavior of the selective dry etching process is discovered and explained, whereby the selectivity has a dramatic increase to as high as 336 when the Sn concentration is above 6%. Different morphologies of suspended microstructures fabricated by different etching methods are investigated. Comparative study shows that the selective dry etching is a better choice for high Sn concentration GeSn (above 7%) against Ge to have better morphology, selectivity and verticality. While for low Sn concentration GeSn (below 6%), wet etching is a better way to fabricate a suspended GeSn microstructure on Ge. This work provides a comparative understanding of both methods of selective etching for GeSn. This comparative understanding is expected to be applied in the processing of next generation electronic and photonic devices.